Manifesto - Blanchard, O. J.; Maskin, E. S.; Summers, L. H. (Quarterly Journal of Economics, 1985)
Olivier J. Blanchard, Eric S. Maskin, Lawrence H. Summers; Manifesto, The Quarterly Journal of Economics, Volume 100, Issue 1, 1 February 1985, Pages iii,